Dilemmas of (Geographical) Environmental Education (Part II) - Köck, Helmuth (Journal of Geography Education, 2003)
Since the 1970s, the environmental awareness has nationally and internationally increased, although there was a certain loss registered in the 1990s. The environmental behaviour correlates extremely weak with it. There is almost a gap or discrepancy between environmental awareness and environmental behaviour. The cause of this discrepancy lies, for the greatest part, in evolutionary motives of human behaviour like, for example, the strive for pleasant sensation or for the experience of pleasure, the self-centred-, now- and here-orientation, but also in poor mental equipment, environmentally hazardous socialisation and ’Enkulturation’, that altogether cause constellations that are like a dilemma for environmentally-oriented behaviour. At the sight of this, there have to be two strategies for the geographical environmental education: on the one hand the environmentally compatible ’lnstrumentalisierung’ of the genetic proneness to action of human beings, on the other hand the education to an environmentally-oriented reflected and controlled contact with this proneness to action. This article moves in this range of problems.